Exploring the Prominent Role of Social Institutions in Society - Baral, Rameshwor (International Research Journal of MMC, 2023)
Social institutions are the patterns that define and regulate the acceptable behavior of individuals within our society. This article aims to explore the prominent role of social institution in society. Family, religion, education, media and government in this article are considered major social institutions that play imperative roles in shaping social norms and values. Family is the first social institution that a person encounters, and it teaches individuals the basic norms and values of their culture. Religion reinforces these norms and values by providing a moral framework and a sense of community. Education shapes social norms by teaching individuals about their society and its history, and it also imparts values such as respect for authority and responsibility. Media, including television, newspapers, and social media, plays a crucial role in shaping social norms and values by disseminating information and influencing public opinion. Government and legal institutions impose social norms through laws and regulations, and shape values through policies and initiatives. This article has been prepared by going through a comprehensive overview of literature reviews regarding social institutions. The qualitative data required for this article have been taken from books and journal articles. Its significance lies in providing structures and patterns that reinforce moral frameworks, rules and regulations required for the cohesion and stability of society.